Modern Approaches to Deviant Behaviour Prevention in Psychological Service Activities - Liudmyla I. Mahdysiuk; Violeta B. Demchuk; Bohdana V. Pavlova (Mukachevo State University, 2021)
The study presents modern approaches to deviant behaviour prevention used by the psychological service. The relevance of this issue is associated with the rapid spread of deviant behaviour among adolescents and youth. The aim of the study is to analyse the peculiarities of the psychological service's activities in the field of working with people with deviant behaviour. The study uses theoretical methods for analysing the researched subject, on the basis of which the prospect of further examination in the empirical area is highlighted. In accordance with the tasks set, the authors analysed the main areas and objectives of the psychological service's activities for today. The study highlights the features of deviant behaviour among adolescents and youth, its main causes. The authors described current approaches to preventing the spread and reduction of deviant behaviour in the work of psychological services. In the course of theoretical research, it was identified that modern approaches to deviant behaviour prevention, which are operated by the psychological service, are characterised by the presence of primary theoretical knowledge among its employees about deviant behaviour features, in particular, the causes and factors of its occurrence. The focus on eliminating and preventing the occurrence of deviant behaviour within the tasks and competencies of the psychological service is substantiated. It is indicated that considering the theoretical foundations of deviant behaviour, employees of the psychological service prepare psychological assistance plan, which provides for systematic, step-by-step preventive services. The study confirms the necessity of using modern preventive approaches, including training sessions, the use of information technologies, and psychological art therapy techniques. This approach, identified as a result of a theoretical study, will ensure the effective prevention of deviant behaviour by psychological service